STRAT EGI PENDIDIKAN KARAKTER PADA MADRASAH Tsanawiyah Muhammadiyah 01 Purbalingga, Jawa tengah - Umi Muzayanah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This study aimed to describe the strategy of integrated character education in madrasah management. This research is a case study done in MTs Muhammadiyah 01 Purbalingga, Central Java, by using descriptive qualitative approach. Data collection was done by interview, observation, and document review. The results showed that (1) strategy of character education through madrasah management has not been implemented to the fullest. In the preparation of planning activities not listed explicitly madrasah character values to be achieved, both in the work plan of the madrasah (RKM) annual and mid-term (four years). In practical terms, this madrasah has internalized the values of character through discipline and self habituation activities; (2) integrated character education strategy in the implementation of learning can be seen in subjects of science, Civics, sosial studies, Quran Hadit, and morals. Internalization of character values is applied to the planning, implementation of learning, through the process of evaluation of learning outcomes; and (3) the strategy of character education through training activities is conducted through extracurricular activities such as scouting, PMR (Youth Red Cross), Pencak Silat Tapak Suci, sports, training for girls, and so forth.